Critical Analysis of Phenomenological Research Design in a Qualitative Research Method - Adeniran , Adetayo Olaniyi; Tayo-Ladega‎, Oluwadamisi (Management Analytics and Social Insights, 2024)
The research method and design have close relationships and are contained in each other. This study critically analyses phenomenological research design in a qualitative research method, intending to expose scholars in management, humanities, business, and social sciences to the dynamics of qualitative research methods and phenomenological research design, especially when conducting phenomenological research. A qualitative phenomenological research design is used to describe previous and present experiences of participants. This study further explains the research design, data collection methods, sample size, data analysis techniques, and roles of researcher, among other areas within the qualitative phenomenological research design, such that the outcome of qualitative phenomenological research will be credible, trustworthy, and dependable.